Gambaran Faktor Lingkungan dan Host pada Pasien Demam Berdarah Dengue di Rumah Sakit Umum Cut Meutia - Wina Adelia Pasaribu; Mauliza Mauliza; Mardiati Mardiati (Pusat riset dan Inovasi Nasional, 2025)
Dengue Hemorrhagic Fever (DHF) is an acute infectious disease caused by the dengue virus and transmitted by the Aedes aegypti mosquito. DHF remains a significant public health concern in Indonesia, including in Aceh Province, which reports a high incidence rate annually. North Aceh ranks seventh in the number of DHF cases among all districts/cities in the province. Transmission occurs through the bite of an infected mosquito or when mosquitoes acquire the virus after biting a viremic individual. This study aims to assess environmental and host factors among DHF patients admitted to Cut Meutia General Hospital. A descriptive study with a cross-sectional design was conducted, involving 38 patients aged 1–17 years hospitalized from January 2019 to December 2021. The findings revealed that 78.9% of patients lived in homes without window screens, and 89.5% had water storage containers in their household environment. Regarding host factors, the majority of patients were aged 11–17 years (65.8%) and male (81.6%), with moderate levels of knowledge (55.3%) and preventive behavior (65.8%) toward DHF. These findings highlight the relevance of environmental and individual determinants in the occurrence of DHF and may inform future disease prevention and control strategies in endemic areas.